ROOT DEVELOPMENT AND GROWTH OF MIXED STANDS OF Eucalyptus urograndis AND Acacia mangium UNDER DIFFERENT TYPES OF SOIL TILLAGE - Cabreira, Gerhard Valkinir; Silva, Eduardo Vinícius; Pereira, Marcos Gervasio; Paula, Tafarel Rodrigues; Cabreira, Wilbert Valkinir (Floresta, 2020)
Atmospheric nitrogen (N)-fixing tree species provide numerous benefits for the soil. The objective of this study was to evaluate the effect of soil management on root development and growth of trees in mixed stands of Eucalyptus urograndis (Eucalyptus urophylla S. T. Blak and Eucalyptus grandis W. Hill ex Maiden) and Acacia mangium Willd. These species were established in a randomized block design with split plots, subjected to minimum tillage and intensive tillage, monospecific stand of Eucalyptus urograndis (1) and Acacia mangium (2), in addition to the intercropping of these species with 50% of the density of the compound compartment of each species (3). Increments in diameter and height were measured up to 49 months after installation of the experiment and fine roots (<2 mm in diameter) were sampled at five different points in two sets of trees per plot up to 1.0 m depth (0-0.1, 0.1-0.3, 0.3-0.5, 0.5-1.0 m) using a steel probe with 0.045 m internal diameter. After 49 months, E. urograndis trees showed greater increments in height and diameter. Treatment 2 showed a higher fine root density (FRD) in all layers. The implementation of mixed stands intensified the FRD of E. urograndis in the 0-0.1 m layer. Effect on root development was observed only in the 0.1-0.3 m layer, where intensive tillage increased FRD in treatment 2. Thus, mixed stands can be an excellent alternative for forest production in areas subjected to soil degradation.